The christian humanism of Gregor Narekatsi - Zakaryan, Seyran (Bulletin of Yerevan University E: Philosophy, Psychology, 2025)
The article discusses an issue related to the evaluation of the worldview and philosophical views of Grigor Narekatsi (951-1003), the greatest poet and philosopher of the Middle Ages, and to clarify it, the concepts of the Middle Ages, Renaissance, Armenian Renaissance, Christian God-centered humanism and Renaissance human-centered humanism are analyzed. Some researchers, referring to Narekatsi's book “The Book of Tragedy”, his innovative thoughts and approaches, the doctrine of the "inner" man and the salvation of man, consider him a representative of the Armenian Renaissance, a forerunner, that is, not a thinker of the Middle Ages, but of the Renaissance era. If in the Soviet period, when the Marxist methodology was in control, the circulation of such narrative was understandable (the theory of the Oriental and Armenian Renaissance was meant to justify the proposition of the Marxist philosophy of history that universal patterns operate with iron necessity in history, for example, all peoples must go through the same stages of development), then it is unclear why researchers today defend this highly ideological and ineffective methodological narrative. According to the author, such narrative is due to the fact that these researchers: a/ essentially ignore the differences between Medieval and Renaissance cultures, as a result of which the phenomena characteristic of medieval culture are presented as renaissance, b/ ignore the peculiarities of Christian God-centered humanism and Renaissance human-centered humanism, c/ Considering Narekatsu as a representative of the Armenian Renaissance, they allegedly give him an assessment corresponding to his genius (in this case it is assumed that the Renaissance era is progressive compared to the Middle Ages). Meanwhile, Narekatsi- the greatest representative of Christian humanism, truly a "Archimandrite of the Universal Church" is a medieval thinker with his vision of human salvation, with his way of thinking, ways of discussing and solving worldview-philosophical issues.
Keywords: Grigor Narekatsi; Middle Ages; Renaissance; Armenian Renaissance; humanism; God-centered humanism and human-centered humanism